ЕVALUATION OF HAZELNUT CLONES AND SORTS OF UKRAINIAN RESEARCH INSTITUTE OF FORESTY AND FOREST MELIORATION BREEDING IN THE “VESELI BOKOVENKY” EXPERIMENTAL BREEDING DENDROLOGIC FORESTRY CENTER - Slusarchuk, V. Y. (Forestry and Forest Melioration, 2018)
The method of hazelnut varieties and clones inventory we are suggesting enables plants differentiation by vitality, a profusion of fruiting, shrubs composition, size and thereby perfects selection of varieties and clones for different purposes, in particular – for vegetative reproduction and further use in order to create plantations for hazelnut production, seed reproduction and use of these plants in a protective afforestation. Testing methods gave the possibility to establish that the following varieties from the hazelnut gene pool of the “Vesely Bokovenky” Experimental Breeding Dendrological Forestry Center are the most appropriate for vegetative propagation and commercial cultivation: ’Borovsky’, ’Stepnoi-83’, ’Shedevr’, ’Koronchatyi’, ’Urozhainyi-80’, ’Podarok unnatam’, ’Michurinets-42’, ’Funduk-85’, ’Badius’, ’Obil’nyi’, ’Veselobokovenkovskyi’, ’Davidovskyi’, ’Dolinskyi’, ’Kirovogradskii’, ’Nakhodka’ and ’Dnepr-1’ as pollinator.